The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude